Alternative Recruitment Strategies Influence Saliva Sample Return Rates in Community‐Based Genetic Association Studies. (14th February 2013) - Bhutta, Mahmood F.; Hobson, Lindsey; Lambie, Jane; Scaman, Elizabeth S. H.; Burton, Martin J.; Giele, Henk; Jamieson, Sarra E.; Furniss, Dominic
Summary Collection of saliva for DNA extraction has created new opportunities to recruit participants from the community for genetic association studies. However, sample return rates are variable. No prior study has specifically addressed how study design impacts sample return. Using data from three large‐scale genetic association studies we compared recruitment strategy and sample return rates. We found highly significant differences in sample return rates between the studies. In studies that recruited retrospectively, overall returns were much lower from families with a self‐limiting condition who provided samples at a research centre or home visit, than adult elderly individuals with a chronic disease who provided samples by post (59% vs. 84%). Prospective recruitment was associated with high agreement to participate (72%), but subsequent low return of actual saliva samples (42%). A telephone call had marginal effect on recruitment in a retrospective family study, but significantly improved returns in a prospective family study. We found no effect upon DNA yield comparing observed versus unobserved sample collection, or between male and female adult participants. Overall, study design significantly impacts upon response rates for genetic association studies recruiting from the community. Our findings will help researchers in constructing and costing a recruitment protocol.